A collaborative professional development on teachers' higher order thinking - Cojorn, Kanyarat (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
This study examines the effectiveness of collaborative professional development (CPD) programs in enhancing teachers’ ability to foster higher-order thinking skills (HOTS) among students. The research adopts a mixed-methods approach, integrating quantitative data from pre- and post-intervention assessments with qualitative insights from teacher interviews and classroom observations. Findings reveal that CPD significantly improved teachers’ pedagogical strategies, particularly in designing inquiry-based tasks, facilitating open-ended questioning, and promoting critical and creative thinking. Moreover, collaborative learning communities provided opportunities for peer feedback, reflective practice, and sustained professional dialogue, which contributed to teachers’ confidence and instructional adaptability. The study underscores the pivotal role of collaborative professional development in building teacher capacity for fostering HOTS and suggests that school systems should institutionalize CPD as a strategic tool for curriculum innovation and student-centered learning.